Continuous assessment in Expressive Arts in Malawian primary schools - Chirwa, Grames Wellington; Naidoo, Devika (The IIE, 2015)
The new Curriculum in Malawi: the Primary Curriculum and Assessment Reform (PCAR) designed on the principles of integrated learning areas; outcomes; learner-centred pedagogies and continuous assessment (CA) was implemented in 2007. The purpose of this study was to investigate Expressive Arts teachers’ understandings, experiences and practices of continuous assessment in a selection of six state primary schools. Within a qualitative research design, and using the concepts of ‘instructional system’ and ‘learning milieu’ of Illuminative evaluation as postulated by Parlett and Hamilton (1976), data were collected through observations, interviews and document analyses. Teachers’ practices were characterised by an informal, technical form of assessment that privileged rote recall of facts and meeting bureaucratic requirements. The teachers cited large classes, lack of material resources and insufficient time as constraints. This study recommends that attention be given towards developing teachers’ understanding of CA principles and practice both at pre-service and in-service levels.
Keywords: Illuminative Evaluation; Formative Assessment; Continuous Assessment; Summative Assessment; Teacher Development; In-service Training; Art Teachers